1996
DOI: 10.1074/jbc.271.27.15858
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-accessible Residues on the Metal Ion-dependent Adhesion Site Face of Integrin CR3 Mediate Its Binding to the Neutrophil Inhibitory Factor

Abstract: Neutrophil adhesion-dependent functions such as chemotaxis, spreading, and phagocytosis are inhibited by neutrophil inhibitory factor (NIF), a glycoprotein produced by the hookworm Ancylostoma caninum. The NIF binding site has been localized to the A-domain of integrin CR3 (CD11b/CD18) and shown to be metal-dependent. The recently solved crystal structure of the A-domain from CD11b revealed a putative metal ion-dependent adhesion site (MIDAS) on the top of the structure. To determine if NIF binds to the A-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 25 publications
3
65
0
Order By: Relevance
“…7B, the binding of the ␣ M I-domain with mutation F246R was reduced significantly. The reduced binding of the three mutants, F246R, D254A, and P257A, to P2-C was apparently not caused by perturbation in conformation based upon the following observations: 1) The reactivity of the mutant I-domains with anti-␣ M I-domain mAbs 44a and 904 was similar to that the wildtype ␣ M I-domain (not shown), consistent with what was reported previously for other mutations in this region (20). 2) Inspection of the three-dimensional structure of the ␣ M I-domain suggested that introduction of these substitutions would not produce conformational changes because side chains of the three mutated residues do not interact with neighboring residues and thus do not contribute into stabilization the overall structure; instead, alanine substitution of Pro 257 should improve the slightly imperfect ␣5 helix.…”
supporting
confidence: 77%
“…7B, the binding of the ␣ M I-domain with mutation F246R was reduced significantly. The reduced binding of the three mutants, F246R, D254A, and P257A, to P2-C was apparently not caused by perturbation in conformation based upon the following observations: 1) The reactivity of the mutant I-domains with anti-␣ M I-domain mAbs 44a and 904 was similar to that the wildtype ␣ M I-domain (not shown), consistent with what was reported previously for other mutations in this region (20). 2) Inspection of the three-dimensional structure of the ␣ M I-domain suggested that introduction of these substitutions would not produce conformational changes because side chains of the three mutated residues do not interact with neighboring residues and thus do not contribute into stabilization the overall structure; instead, alanine substitution of Pro 257 should improve the slightly imperfect ␣5 helix.…”
supporting
confidence: 77%
“…In support of our findings, while our study was in progress, Rieu et al (26) recently identified several specific residues which are important for NIF-␣ M ␤ 2 interaction. Their study implicated residues (26) found that mutation of these two residues disrupted NIF binding, whereas we found that the Glu 178 -Tyr 185 segment which contains these residues, was nonessential. As one possible explanation, in the study of Rieu et al, Glu 178 -Glu 179 both were mutated to Ala, whereas we changed them to Thr and Ser, corresponding to their homologous sequences in ␣ L ; the former substitutions may indirectly disrupt the conformation of the spatially adjacent loop between helix 3 and 4 (see Fig.…”
Section: Discussionmentioning
confidence: 62%
“…4C). Although specific residues around the metal ion-dependant adhesion site must contribute some specificity to the wide range of ligands recognized (35)(36)(37), the findings suggest that the promiscuous ligand recognition by ␣ X ␤ 2 and ␣ M ␤ 2 is primarily because of high affinity for acidic side chains. Other cell adhesion receptors such as CD2 rely on ligand affinities in the order of 100 M (38), and therefore both the low-and highaffinity sites on Fg for the ␣ M and ␣ X I domains are in a physiologically meaningful range.…”
Section: Neutrophil Adhesion To Protease-digested Fgmentioning
confidence: 89%